2012
DOI: 10.1021/om300121c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Lactide Polymerization with Lithium, Sodium, Magnesium, and Calcium Complexes of BHT

Abstract: A series of Li, Na, Mg, and Ca complexes with 2,6-di-tertbutyl-4-methylphenol (BHT) as the ligand has been synthesized, and their reactivity for the ring-opening polymerization of lactide has been studied. The Ca complex with 2,2′-ethylidenebis(4,6-di-tert-butylphenol) (EDBP) as the ligand also has been synthesized to compare with the BHT systems. All complexes, in the presence of benzyl alcohol as initiator, exhibit high activity for the ring-opening polymerization of lactide. Polymerization activities follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 55 publications
1
55
1
Order By: Relevance
“…Nevertheless, some tin compounds have appreciable cytotoxicity and are susceptible to atmospheric conditions which increase the production expenses . In this regard, research is now exploring the use of other organometallic compounds with lower toxicity such as alkali metals, magnesium, calcium, zinc, copper, iron, and aluminum all of which have shown promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some tin compounds have appreciable cytotoxicity and are susceptible to atmospheric conditions which increase the production expenses . In this regard, research is now exploring the use of other organometallic compounds with lower toxicity such as alkali metals, magnesium, calcium, zinc, copper, iron, and aluminum all of which have shown promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number of aryloxide complexes of main group and transition metals has increased dramatically in recent years. ortho-Disubstituted bulky phenols, including 2,6-di-tert-butyl-4-methylphenol (butylated hydroxytoluene or BHT-H), have been used successfully to synthesize highly active catalysts for the ROP of rac-lactide, "-caprolactone and !-pentadecalactone (see Chen et al, 2012;Fang et al, 2012;Ivchenko et al, 2017;Nifant'ev et al, 2016Nifant'ev et al, , 2017aWilson et al, 2014Wilson et al, , 2015, and references therein) or cyclic phosphoesters (Nifant'ev et al, 2017c, 2018). We report herein the synthesis and structures of ISSN 2053ISSN -2296 # 2018 International Union of Crystallography Mg, Al and Zn complexes (Scheme 1) and present results on the ROP of "-caprolactone ("-CL) associated with these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Mg(BHT) 2 (THF) 2 itself (THF is tetrahydrofuran) is catalytically inactive but displays high catalytic activity in the polymerization of cyclic esters when activated by alcohols (e.g. Chen et al, 2012), whereas the [Mg(BHT)(OR)(THF) n ] 2 complexes (n = 0 or 1) do not require an initiator for the ROP process to occur (Nifant'ev et al, 2016(Nifant'ev et al, , 2017d. The reaction of either Mg(BHT) 2 (THF) 2 or Mg(BHT)(n-Bu)(THF) 2 with 1 molar equivalent of a primary alcohol allowed us to prepare dimeric complexes possessing definite compositions and established crystal structures [ Fig.…”
Section: Introductionmentioning
confidence: 99%
“…ortho-Disubstituted bulky phenols, including BHT-H (BHT-H is butylated hydroxytoluene or 2,6di-tert-butyl-4-methylphenol), have been used successfully to produce highly effective ROP catalysts. For example, the complexes (BHT) 2 Mg(THF) 2 (Calabrese et al, 1988; THF is tetrahydrofuran), n BuMg(BHT)(THF) 2 and [(-EtO)Mg-(BHT)(THF)] 2 (Nifant'ev et al, 2016), activated with alcohols, have demonstrated high efficiency in the ROP of lactide, "-caprolactone and !-pentadecalactone (Nifant'ev et al, 2016;Wilson et al, 2014Wilson et al, , 2015Fang et al, 2012;Chen et al, 2012). Using [(-RO)Mg(BHT)(THF)] 2 [R = Et or benzyl (Bn)] as examples, it has been demonstrated that activation with an alcohol is not necessary if both phenoxy and alkoxy groups are present within the same Mg complex (Nifant'ev et al, 2016(Nifant'ev et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%